2015
DOI: 10.1186/s40529-015-0089-3
|View full text |Cite
|
Sign up to set email alerts
|

Six new species of Begonia (Begoniaceae) from limestone areas in Northern Vietnam

Abstract: BackgroundSpecies of Begonia are richly represented in limestone karst areas across the Sino-Vietnamese border. More than one hundred species were known, many of which were documented recently.ResultsIn continuation of our systematic studies of Asian Begonia, we report six species of Begonia that are unknown to science, namely B. caobangensis [sect. Platycentrum], B. circularis, B. melanobullata, B. langsonensis, B.locii and B. montaniformis [sect. Coelocentrum] from Northern Vietnam. Diagnostic features that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 7 publications
2
27
0
Order By: Relevance
“…In the latter species, the petals are covered abaxially by brown pubescence and are much larger than those of the new species. As to the lanceolate and colourful leaves, the new species is similar to Begonia locii C.-I Peng, C. W. Lin & H. Q. Nguyen, but different in the absence of glandular hairs of flowers (Peng et al 2015a). Furthermore, as to the glandular pubes, the new species is also similar to B. filiformis Irmsch., but differs in the subglabrous adaxial surface and laxly pubescent abaxial surface of leaves ( vs. densely pubescent adaxial and abaxial surface of leaves in the latter).…”
Section: Taxonomymentioning
confidence: 87%
See 2 more Smart Citations
“…In the latter species, the petals are covered abaxially by brown pubescence and are much larger than those of the new species. As to the lanceolate and colourful leaves, the new species is similar to Begonia locii C.-I Peng, C. W. Lin & H. Q. Nguyen, but different in the absence of glandular hairs of flowers (Peng et al 2015a). Furthermore, as to the glandular pubes, the new species is also similar to B. filiformis Irmsch., but differs in the subglabrous adaxial surface and laxly pubescent abaxial surface of leaves ( vs. densely pubescent adaxial and abaxial surface of leaves in the latter).…”
Section: Taxonomymentioning
confidence: 87%
“…After review of the type specimens and taxonomic publications within the regions (Gagnepain 1921; Irmscher 1939; Ho 1991; Nguyen 2004; Shui and Chen 2005; Truong et al 2005; Nguyen and Tebbit 2006; Kiew 2007; Nguyen et al 2010; Peng et al 2014, 2015a,b; Hughes et al 2015), seven new species of Begonia have been confirmed, and their sectional positions designated here (Doorenbos et al 1998; Shui et al 2002). Due to the taxonomic complexity of the genus (Thomas et al 2011; Chung et al 2014), the DNA samples of the above new species have also been collected and some possible different opinions will be issued about their systematic position in the broad context in the future.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Limestone outcroppings support tropical forest biodiversity at low latitudes around the globe (Felfili et al 2007). Tropical forests on limestone are viewed as relict communities, with many endemic and new species (Musser et al 2005;Crottini et al 2011;Bogutskaya et al 2012;Chen et al 2014;Peng et al 2015). Natural environmental factors and human activities have complex negative and positive effects on the biodiversity of these unique environments.…”
Section: Introductionmentioning
confidence: 99%
“…China, after Brazil, has the second largest number of Begonia species, with 173 species recorded in Flora of China and 141 endemic in China (Gu et al 2007). After publication of Flora of China, 14 new Begonia species, all endemic in China, are described and illustrated (Ku et al 2008, Li et al 2008, Liu et al 2007, Ma et al 2006, Peng et al 2008a, 2008b, 2009, 2010, Shui 2007, Wei et al 2007). There are still many potential new taxa under investigation, therefore, the total number of Begonia species in China could easily reach over 200.…”
Section: Introductionmentioning
confidence: 99%